Development of lignin-based polyurethane thermoplastics - Pong, Rachel Ruici (Nanyang Technological University, 2022)
Traditional polyurethane synthesis involves the use of petroleum-based polyols, which raises environmental concerns. In recent years, research efforts have been dedicated to finding alternative bio-based sources of polyols. Here, lignin-based thermoplastic polyurethanes were prepared from alkali lignin, poly(ε-caprolactone) diols of different molecular weights of 530 and 2000 Da), and hexamethylene diisocyanate. Secondary polyols including polyethylene glycol (PEG), and polydimethylsiloxane (PDMS), were incorporated into the polyurethane formulations to tune their properties. The chemical structures of the lignin-based polyurethanes were characterised by NMR, FTIR and GPC, while their thermomechanical properties were analysed by TGA, DSC, uniaxial tensile testing and DMA. We found that the lignin-based synthesised from PCL2000 show higher molecular weight and superior mechanical properties compared to the lignin-based PU from PCL530. Among all the samples, the lignin-based PU with PCL 2000 Da displays the best mechanical properties with tensile strength reaching 13.7 ± 4.1 MPa and elongation reaching 884 ± 381 %. We also found that the addition of 5 wt.% of PDMS or PEG in the PCL2000 series decreases the tensile strength and elongation at break of the lignin-based PU films. Biodegradation studies revealed a slightly lower susceptibility of lignin-based PUs containing PDMS to esterase-catalysed degradation. Lignin-based PUs prepared with 2000 Da also demonstrated better UV stability.